2018
DOI: 10.1007/s10534-018-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic mercury in human astrocytes, oligodendrocytes, corticomotoneurons and the locus ceruleus: implications for multiple sclerosis, neurodegenerative disorders and gliomas

Abstract: Neurotoxic metals have been implicated in the pathogenesis of multiple sclerosis, neurodegenerative disorders and brain tumours but studies of the location of heavy metals in human brains are rare. In a man who injected himself with metallic mercury the cellular location of mercury in his brain was studied after 5 months of continuous exposure to inorganic mercury arising from metallic mercury deposits in his organs. Paraffin sections from the primary motor and sensory cortices and the locus ceruleus in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 61 publications
2
34
0
1
Order By: Relevance
“…Our findings of mercury adjacent to the nuclei of oligodendrocytes recapitulates findings in the cerebral cortex from this man who injected himself with metallic mercury [40], as well as ultrastructural studies of rats exposed to mercury which showed mercury binding to oligodendrocyte nuclear membranes [34] and lysosomes [36]. Mercury in oligodendrocytes could affect myelin metabolism and axonal conductance, which has the potential to slow nerve impulses from the geniculate nuclei to their respective primary cortices.…”
Section: Plos Onesupporting
confidence: 84%
“…Our findings of mercury adjacent to the nuclei of oligodendrocytes recapitulates findings in the cerebral cortex from this man who injected himself with metallic mercury [40], as well as ultrastructural studies of rats exposed to mercury which showed mercury binding to oligodendrocyte nuclear membranes [34] and lysosomes [36]. Mercury in oligodendrocytes could affect myelin metabolism and axonal conductance, which has the potential to slow nerve impulses from the geniculate nuclei to their respective primary cortices.…”
Section: Plos Onesupporting
confidence: 84%
“…Because AD patients display altered metal dyshomeostasis [64] that manifests in different ways, including altered plasma/CSF (cerebrospinal fluid) ratios for various metal ions including Hg(II), it has been suggested that AD pathology may involve a compromised blood-CSF barrier [93,137]. On the other hand, the brain metal chemistry is notoriously complex, and studies on beluga whales and humans indicate that Hg(II) and other metal ions accumulate into different brain regions also for non-AD individuals [138][139][140]. One study with a limited number of patients reported elevated Hg concentrations in the two brain regions nucleus basalis of Meynert (NBM) and amygdala [135].…”
Section: Mercury and Ad: Clinical Studies And Sources Of Exposurementioning
confidence: 99%
“…Astrocytes has been postulated in a primary role of MS [22]. Recently, inorganic mercury was found in astrocytes from autopsy-obtained tissue from a man who injected himself intravenously with metallic mercury [23]. This provides the direct evidence that mercury could play a role in the pathogenesis of MS.…”
Section: Discussionmentioning
confidence: 91%